Efeitos do ácido zoledrônico na consolidação de fraturas na diáfise dos fêmures de ratos osteoporóticos tratados com osteossíntese intramedular - Rocha, Sânia Nara Costa (2018)
With the inversion of the population pyramid there was an increase in the incidence of diseases that occur with aging, especially osteoporosis. It is a disease characterized by a reduction of bone resistance, increasing the susceptibility of the individual to the occurrence of fractures. Falls in the elderly with osteoporosis often lead to reduced quality of life, loss of independence, hospitalization, loss of functional abilities and have a great economic impact. Treatment should be based on the pathophysiology of the disease, and there should be decreased osteoclast activity and / or increased osteoblast activity. Clinical studies have shown that the use of bisphosphonates reduces the risk of femoral fractures in osteoporotic patients. The bisphosphonate chosen for study in the present study was zoledronic acid (AZ). The present study had as objective to verify the effects of AZ in the consolidation of diaphyseal fracture of femurs of osteoporotic rats submitted to intramedullary osteosynthesis. The sample consisted of 36 adult male wistar rats weighing 250-300g. The animals were divided into two groups: control and AZ. E were subdivided into three groups, according to the period of bone consolidation (7,14 and 28 days). In all animals, hydrocortisone was administered for a period of 28 days for the purpose of inducing osteoporosis. After this period, the production of femoral shaft fracture and intramedullary osteosynthesis were performed in all groups. The AZ group received 0.1 mg / kg of the acid intraperitoneally and the control group received saline. Radiological and histological studies were performed. In the radiological study, the area of the bone callus was quantified. The histological study was carried out to quantify the formation of collagen type I and type III in the cortical region close to the fracture and in the bone callus. Regarding the area of bone callus, in the intergroup analysis, statistically significant differences were observed in the group treated with AZ. The 7-day group treated with AZ was significantly lower than the control group (p = 0.035), with no significant difference between these two groups on days 14 (p = 0.398) and 28 (p = 0.711). As in the comparisons within the same group, a statistically significant difference was observed in both the control group (p = 0.020) and the AZ group (p = 0.037), showing a statistically significant increase in bone call volume from day 7 to day 28. Zoledronic acid promoted a slight increase in bone callus in the 28-day group of AZ (intragroups). Regarding the percentage of collagen type III, there was a reduction of this type of collagen in the AZ group (intergroups). In the percentage of collagen type I there was no statistically significant result.